Health Practitioner Burnout, Safety Implications, and Programmatic Fixes: A Systematic Literature Review of Current Literature Reviews—200 Proof* - Ralph, J Johnson (Journal of Public Health International, 2025)
High rates of workplace psychological stress and burnout have been chronic among Healthcare Practitioners. Research shows that Healthcare Practitioner psychological stress / burnout is related to poor quality of care and a high probability of making medical errors and mishaps resulting in harm to patients and even workers themselves. In response, relatively impactful programs have been developed to address Practitioner burnout. To derive a better understanding of the subject and inform best practices and policy regarding the problem and its fixes, this article reports findings from a novel study of a systematic (PRISMA-based) literature review of current (circa ~10 years <) literature reviews; or a distillation of reviews already at 100 proof then undergoing a further distillation into a review of 200 proof.* This study employed a grounded theoretic qualitative methodology to iteratively generate and enumerate descriptive themes from the study’s literature review articles. This article reports on what is currently known regarding the precipitants of Health Practitioner Burnout, Burnout itself, its relationship to Safety lapses and mishaps, and Programmatic Interventions (i.e., Fixes). The primary conclusion is that Health Practitioners are the foundation of healthcare organizations and key to quality care and management / leadership should be concerned for their wellbeing; and this article provides a general blueprint in terms of addressing burnout and safety. Study Limitations and Future research are also discussed.
Keywords: Health Care Practitioners; Health Workers; Psychological Stress; Burnout; Safety; Adverse Events; Interventions; CBT; Mindfulness; Resilience; Culture of Safety